IMPRESSION IN “I WANDERED LONELY AS A CLOUD” - Nugroho, Henriono (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 16 (2009): March 2009, 2009)
Abstract Stylistics is a linguistic analysis on literary and non-literary texts. This article concerns with a systemic stylistic analysis on a poem in terms of Systemic Functional Linguistics and Verbal Art Semiotics. The article uses library research, qualitative data, documentary study, descriptive method and intrinsic-objective approach. The semantic analysis results in both automatized and foregrounded meanings. Then the automatized meaning produces lexical cohesion and in turn, it produces subject matter. Meanwhile, the foregrounded meaning produces the literary meaning and in turn, it creates theme. Finally, the analysis indicates that the subject matter is about the beautiful daffodil, the literary meaning is about the impressive flower and the theme is about impression of dancing daffodils.